Critical factors in determining customer satisfaction toward internet shopping in Malaysia - Nikhashemi, Seyed Rajab; Paim, Laily; Yasmin, Farzana; Yousefi, Abdolaziz (International Journal of Business and Management Invention, 2013)
Customer satisfaction is one of the greatest influential forces in the internet shopping in today’s marketplace and emerging as the strategic imperative for the 1990s. In this study, we proposed four critical factors which have great effect on customer satisfaction in regards to the internet shopping. A survey was conducted to gather data to test the relationships in the proposed model. The collected primary surveys (n =218) are accompanied to examine the influence of the four dimensions expressed in the proposed structural model, therefore regression analysis were used to analyze the data. The result of study shows that ease of use, security, payment processing and customer perceived quality have significant positive effect on enhancing customer satisfaction toward internet shopping.